PENYELESAIAN PERKARA TINDAK PIDANA PERS MELALUI DEWAN PERS SEBAGAI LEMBAGA MEDIASI - Unu Putra Herlambang, Nyoman Serikat , Endah Sri Astuti (Diponegoro Law Journal, 2012)
Penal mediation is an alternative dispute resolution (ADR) using the principle of win-win solution. In Indonesia about the alternative settlement of criminal cases there has been no regulation governing expressly. However, in matters of criminal cases concerning the proclamation of the journalistic, penal mediation accommodated by Act No. 40 on 1999 of Press. The Press Council as an institution of mediation dispute hearing complaints is authorized as long as it has not yet reported on the police. The basic idea of the creation of the institution of an independent Press Council is to develop freedom of the press in a democratic country Indoenesia. In carrying out its function and role as a jurnalist, the potential for the emerge of the dispute due to the very high journalistic coverage. Not a few who feel aggrieved parties choose criminal law as instruments of dispute resolution. Criminalization of cases the preaching, for the press, the people regarded as restricting press freedom. Therefore, the mediation of press criminal cases through the Press Council is in line with the development of press freedom.